2020
DOI: 10.1177/1077559520912342
|View full text |Cite
|
Sign up to set email alerts
|

Parental Exposure to Childhood Maltreatment and Offspring’s Mental Health: Investigating Pathways Through Parental Adversity and Offspring Exposure to Maltreatment

Abstract: Parental exposure to child maltreatment (CM) is an important predictor of their offspring’s CM experiences and mental health. However, less attention has been paid to examine possible mechanisms of transmission, which is critical to inform prevention and intervention efforts. The current study tested (1) whether the association between parental CM exposure and offspring CM exposure was mediated by (a) parental exposure to violence in adulthood or (b) other emotional stressors/adversities in adulthood and (2) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
(83 reference statements)
1
12
0
Order By: Relevance
“…The present findings support our first hypothesis, as depression emerged as a risk factor and parent–child connectedness as a protective factor in the associations between parental maltreatment history and maltreatment in their child. Our findings are in line with those reported in studies from Burundi and other regions that have demonstrated a link between parental and offspring maltreatment experiences (Crombach & Bambonye, 2015; Morelli et al., 2021; Negriff et al., 2020). The present research also adds to the extant literature by highlighting the roles of depression and parent–child connectedness, which can facilitate clinical interventions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present findings support our first hypothesis, as depression emerged as a risk factor and parent–child connectedness as a protective factor in the associations between parental maltreatment history and maltreatment in their child. Our findings are in line with those reported in studies from Burundi and other regions that have demonstrated a link between parental and offspring maltreatment experiences (Crombach & Bambonye, 2015; Morelli et al., 2021; Negriff et al., 2020). The present research also adds to the extant literature by highlighting the roles of depression and parent–child connectedness, which can facilitate clinical interventions.…”
Section: Discussionsupporting
confidence: 92%
“…The present findings warrant replication in a longitudinally designed study, as PTSS and aggression can be both a consequence of and risk factor for maltreatment in children (Rodriguez et al., 2019). Notably, the findings from a recent longitudinal study examining intergenerational transmission of maltreatment demonstrated that maltreatment in children was prospectively associated with mental health outcomes, including PTSS, depression, and externalizing problems in adolescence (Negriff et al., 2020); however, the study did not consider mental health outcomes as potential risk factors related to CM.…”
Section: Discussionmentioning
confidence: 99%
“…More than half (56%) of adolescents in the sample met the clinical cut off for PTSD, well above the national estimated lifetime prevalence of PTSD in adolescents (5%; National Institute of Mental Health, 2021). Given that we assessed this relation using a composite ACE score, it is difficult to compare with prior literature focused primarily on child maltreatment (e.g., Negriff et al, 2020). Current findings suggest that adolescents reared by caregivers with a history of ACEs may experience higher levels of PTSD symptoms, reinforcing Masten and Cicchetti (2016) emphasis on delineating multiple intergenerational risk pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Although prior research has established that caregiver ACE exposure increases the risk of child ACEs (e.g., see Narayan et al, 2021 for a review; Schickedanz et al, 2021), only one study to the authors’ knowledge has explored the indirect effect from caregiver early adversity to their child’s mental health outcomes via child adversity (Negriff et al, 2020). However, as previously mentioned, this study only focused on experiences of maltreatment (i.e., physical, sexual, and emotional abuse, and physical neglect) as opposed to a wider range of ACEs.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…ACE, namely parental exposure to childhood maltreatment, is an important predictor of maltreatment experiences and mental health problems in the offspring. In particular, considering that maltreatment of the parents in their childhood is significantly related to PTSD symptoms in their offspring [7], maternal ACEs are a risk factor for PTSD not only in the mothers but also in their offspring. However, the association between maternal ACEs and PTSD in the offspring has not yet been examined.…”
Section: Introductionmentioning
confidence: 99%